Education in the Digital Age: An Analysis of the Impact of Technology Integration in Learning on Improving Academic Quality and Social Skills of Students in Elementary School - Mohamad Idhan; Sudirman Sudirman; Zulfitri Zulfitri; Nurzamsinar Nurzamsinar (Journal of Pedagogi, 2025)
The digital era has brought fundamental changes in education, particularly in the way students learn and teachers teach. This study aims to analyze the impact of technology integration in learning on improving students' academic quality and social skills in primary schools in the digital era. Digital transformation in education has brought significant changes in teaching methods, interaction between students and teachers, and students' learning patterns. Through a qualitative approach with literature study and structured observation in several elementary schools, this research found that the appropriate use of technology can improve concept understanding, accelerate access to information, and facilitate more personalized and adaptive learning. In addition, the integration of collaborative platforms and digital media also promotes the development of social skills such as communication, cooperation and empathy. However, the effectiveness of technology integration is highly dependent on infrastructure readiness, teacher competence, and proper guidance so that students do not get trapped in digital isolation. In conclusion, the integration of technology in primary school learning has great potential to support a more holistic transformation of education, not only improving academic quality, but also shaping a young generation that is socially competent and ready to face the challenges of the 21st century. This study recommends the importance of collaboration between education stakeholders, improving teachers' competencies and developing a contextualized digital curriculum as part of a long-term strategy in realizing quality and sustainable basic education